Achieving Ukraine's Agricultural Potential : Stimulating Agricultural Growth and Improving Rural Life - World Bank (Washington, DC, 2013)
This study provides a review of the food and agricultural sector in Ukraine. It assesses the current status of the food and agricultural sector with special reference to the agricultural policy regime and the form and level of government support to the sector. The paper reviews the sector's readiness to compete on open global markets for food and agricultural products. Given the importance and sensitivity of the food and agriculture sector in the country, the report highlights a number of critical issues for the Ukrainian government to address. The report goes beyond the narrower focus of the agricultural policies and reviews the status of current rural physical and social infrastructure and issues of rural poverty. The Executive Summary highlights policy recommendations for Ukrainian policymakers, while the individual chapters provide technical analysis on key policy issues.